SMART ROOM MONITORING MENGGUNAKAN MIT APP INVENTOR DENGAN KONEKSI BLUETOOTH - Micha Thesania Katarine; Karel Octavianus Bachri (Jurnal Elektro, 2020)
This study aims to design a smart room monitoring system (smart room) to determine the condition of the room in the house. This smart room system is based on Bluetooth and is assisted by the MIT App Inventor application which can do remote monitoring. This system is controlled by the Arduino Mega microcontroller which is connected to the sensor and Bluetooth. The sensors used are MQ2 to detect gas leaks, LM35 to detect room temperature, and PIR sensors to detect human presence. The MQ2 Sensor is placed near the LPG gas canisters, the PIR sensor is placed at entrance, while the LM35 sensor is placed at the center of the room, with neither direct blow from the Air Conditioner nor direct exposure to sunlight. Experiment shows that the sensor and the system work, and the application can also be connected to the system so that the sensors are monitored. In the MIT App Inventor application, the data received from Bluetooth is a PIR sensor that detects the presence of people in the room, the LM35 sensor can detect room temperature, and the MQ2 sensor can detect the presence of leaking gas.